Utilization of modified corn stover powder as sustainable binder into eco-friendly mortar - Zhi-hai He; Di-ping Hong; Yuan-yuan Jiang; Wen-qiang Zhai; Rui-qian Wu; Wei Tang; Bao-ju Liu (Results in Engineering)
Corn stover powder is a type of agricultural waste, and its incineration causes several problems, such as environmental pollution and resource waste. Therefore, it is imperative to address the resource utilization problem of corn stover powder. In this study, modified corn stover powder (MCSP) is prepared by calcining corn stover powder at 600 °C for 2 h. The effects of MCSP as a supplementary cementitious material on the fluidity, setting time, compressive strength, shrinkage and microstructure of cement-based materials are investigated, and the corresponding ecological evaluation is conducted. The findings demonstrated that with the MCSP dosage increases, the fluidity of the mortar reduces and the setting time of the pastes generally shortens. Meanwhile, incorporating 5 % MCSP improves the 28-d compressive strength of the mortar by 18.4 % compared with the ordinary mortar. Incorporating 5 % MCSP refines the pore structure of mortar and increases the hydration product content, thus decreasing the drying shrinkage of the mortar. The autogenous shrinkage of the mortar decreases with increasing MCSP dosage. Furthermore, the cost, CO2 emission and energy consumption of the MCSP mortar decrease with MCSP dosage increasing. The recycling of MCSP is beneficial to produce green and low-carbon mortar.